2011
DOI: 10.1200/jco.2010.33.4714
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Locoregional Recurrence for Women With T1-2N0 Triple-Negative Breast Cancer Treated With Modified Radical Mastectomy Without Adjuvant Radiation Therapy Compared With Breast-Conserving Therapy

Abstract: Women with T1-2N0 TNBC treated with MRM without RT have a significant increased risk of LRR compared with those treated with BCT. Prospective studies are warranted to investigate the benefit of adjuvant RT after MRM in TNBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
232
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(263 citation statements)
references
References 29 publications
(19 reference statements)
16
232
2
5
Order By: Relevance
“…They concluded that breast cancer subtypes may help guide which patients need more aggressive local intervention. Contrary to this, it was shown that T1-2, N0 TNBC patients managed with BCT had low locoregional recurrence rate in comparison with patients in same stage managed with modified radical mastectomy (Abdulkarim et al, 2011;Adkins et al, 2011) in their study on outcomes of BCT versus mastectomy in 1325 patients with TNBC showed no benefit of mastectomy over BCT. There was improved 5 year LRRFS (76% vs 71%), distant metastasis free survival (68 vs 54) and overall survival (74 vs 63) for patients who received BCT.…”
Section: Discussionmentioning
confidence: 89%
“…They concluded that breast cancer subtypes may help guide which patients need more aggressive local intervention. Contrary to this, it was shown that T1-2, N0 TNBC patients managed with BCT had low locoregional recurrence rate in comparison with patients in same stage managed with modified radical mastectomy (Abdulkarim et al, 2011;Adkins et al, 2011) in their study on outcomes of BCT versus mastectomy in 1325 patients with TNBC showed no benefit of mastectomy over BCT. There was improved 5 year LRRFS (76% vs 71%), distant metastasis free survival (68 vs 54) and overall survival (74 vs 63) for patients who received BCT.…”
Section: Discussionmentioning
confidence: 89%
“…Multiple studies have indicated a strong prognostic relation between patients with TNBC and increased LRR, and this also applied to early stage breast cancer. [10][11][12][13]18 In patients with ETNBC, Abdulkarim et al 14 recently reported that the LRR risk in the modified radical mastectomy without PMRT group was 2.5 times higher than in the breast-conserving therapy group among those with T1-T2N0 disease (4% vs 10%; P 5 .027). This has sparked an intense debate about re-evaluating the role of PMRT for ETNBC, a subgroup for which it was previously assumed that PMRT was not clearly indicated.…”
Section: Discussionmentioning
confidence: 99%
“…More studies since have demonstrated that patients who have TNBC are at a higher risk of LRR, 10,11 including those who have very early disease. 12,13 Moreover, in a recent article by Abdulkarim et al 14 reporting exclusively on TNBC, the highest LRR rates were observed in patients who underwent modified radical mastectomy without PMRT compared with those who underwent modified radical mastectomy and received PMRT or breast-conserving therapy. This highlights the need to re-evaluate prognostic factors in early stage TNBC (ETNBC) and the utility of PMRT.…”
Section: Introductionmentioning
confidence: 99%
“…Three retrospective studies have examined the incidence of local failure in TNBC after BCT or mastectomy and found no difference based on surgical procedure, suggesting that these local recurrences are more likely a result of aggressive biology, not residual tumor at the surgical site, which could be improved with wider lumpectomy margins. 29,[37][38][39] This theory is supported by the approximately 40 % decline in IBTR seen in patients with HER2-positive tumors receiving adjuvant systemic trastuzumab and other HER2-targeted agents. 29 In summary, the MP concluded that although there is evidence that the risk of IBTR varies by subtype based on the results of many studies, patients with aggressive tumors remain at equally increased risk for local failure irrespective of treatment with mastectomy or BCT, indicating there is no justification for more widely clear margins over no ink on tumor for any BC subtype.…”
Section: Median Year Of Recruitmentmentioning
confidence: 95%